Synthesis of cadmium oxide nanostructures by using Dalbergia sissoo for response surface methodology based photocatalytic degradation of methylene blue. (10th September 2022) - Haider, Sajjad; Uddin Khan, Salah; Najeeb, Jawayria; Naeem, Sumaira; Rafique, Hummera; Munir, Hira; Al-Masry, Waheed A.; Nazar, Muhammad Faizan
Abstract: In this study, the synthesis of cadmium oxide (CdO) nanostructures (NSs) was carried out by utilizing the leaf extract of Dalbergia sissoo . The as-prepared CdO-NSs were analyzed via techniques of Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction analysis (XRD), and ultraviolet–visible spectroscopy (UV-VIS). The morphological characteristics revealed that highly crystalline cauliflower-like NSs were prepared by using this methodology. The XRD results indicated that the estimated average particle size of the synthesized CdO-NSs was found to be 42.73 nm, which is well supported by the SEM micrographs as well. The applicability of the CdO-NSs as a photocatalyst was studied by performing the model light-driven degradation reaction of methylene blue (MB) dye. The reaction was optimized by using the traditional one-variable-at-a-time (OVAT) approach and advanced response surface methodology (RSM) based statistical approach. The acquired results were compared to investigate the best possible strategy for the optimization of the photocatalytic reaction of MB performed by using the photocatalyst of CdO-NSs. The maximum percentage degradation (%D) values of 92.41% and 96.248% were observed for the OVAT and RSM based approach respectively indicating that RSM based approach is more efficient in optimizing this reaction. Additional information (such as the reaction follows the second-order polynomial model and the reaction variable of initial CdO-NSs dose is the most essential parameter for modulating the %D values of this reaction) was also attained by using the RSM approach. The stability studies reveal that the NSs only suffer up to ≈ 3% decrease in the %D value after five consecutive runs. The total organic carbon (TOC) analysis value of ≈ 93% also reveals that efficient mineralization is achieved under optimized conditions. The synthesized CdO-NSs are extremely stable and are found to be efficient photocatalytic materials for the degradation of MB. Graphical abstract: Image 1 Highlights: The CdO-NSs exhibiting the cauliflower like morphology were engineered by using the Dalbergia sissoo extract. The CdO-NSs were characterized by the techniques of UV-VIS, XRD, BET, FTIR, and SEM analysis. The photocatalytic degradation of the MB in the presence of CdO-NSs was optimized by using OVAT and RSM approach. The RSM was found to be better optimization approach as the %D was improved from 92.41% to 96.24%.